Zinc source influences the gene expression of zinc transporters in jejunum and cecal tonsils during broiler challenge with Eimeria maxima and Clostridium perfringens. (4th October 2018) - He, B; Bortoluzzi, C; King, W D; Graugnard, D; Dawson, K A; Applegate, T J
ABSTRACT: The objective of this experiment was to study the effects of dietary zinc (Zn) source on gene expression of Zn transporters (metallothionein [MT], ZIP 3, 5, 8, 9, 10, 11, 13, and 14, and ZnT 1, 4, 5, 6, 7, 9, and 10) in the jejunum and cecal tonsils of broilers challenged with coccidia or coccidia plus Clostridium perfringens . A 2 × 2 factorial design was used with 2 Zn sources (90 mg Zn/kg from either ZnSO4 or an organic Zn, Bioplex ® Zn) and challenged with approximately 5, 000 oocysts of Eimeria maxima at 14 d of age with or without C. perfringens (10 8 CFU/bird) at 18, 19, and 20 d of age (8 pens per treatment and 8 birds per pen) after which 1 bird/pen was sampled at 21 d of age. In the jejunum, co-infection resulted in higher ZnT 5 and 6 gene expression, while organic Zn fed birds had lower ZIP 5 and 11, and higher ZnT1. Additionally, an interaction of challenge by Zn source was noted wherein ZnT10 was unaffected by the C. perfringens in the organic Zn treatment but was 2.7-fold lower in the co-infected ZnSO4 fed birds. S100A9 gene expression, a biomarker of inflammatory response in necrotic enteritis, increased 2 and 2.8-fold in the cecal tonsils and jejunum with the co-infection, respectively. Supplementation with organic Zn lowered S100A9 by 1.9 and 4.4-fold in the cecal tonsils and jejunum, respectively, when birds were supplemented with ZnSO4 . Notably, MT, ZIP 3, 8, 9, 10, 13, or 14, and ZnT 4, 7, and 9 were unaffected by Zn source and/or method of challenge. An interaction of challenge by Zn source was also noted for serum Zn concentration, which was reduced when birds were challenged with C. perfringens and fed ZnSO4 but no difference between challenge method when birds were fed organic Zn. Based on the expression of ZnT and ZIP genes, more Zn trafficking due to treatment occured in the jejunum than cecal tonsils, but further studies are needed to ascertain how Zn source regulates intracellular free Zn concentrations and whole-body Zn status during an enteric challenge.